2015
DOI: 10.1038/tp.2015.3
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal maternal depression alters amygdala functional connectivity in 6-month-old infants

Abstract: Prenatal maternal depression is associated with alterations in the neonatal amygdala microstructure, shedding light on the timing for the influence of prenatal maternal depression on the brain structure of the offspring. This study aimed to examine the association between prenatal maternal depressive symptomatology and infant amygdala functional connectivity and to thus establish the neural functional basis for the transgenerational transmission of vulnerability for affective disorders during prenatal developm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
228
1
3

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 240 publications
(249 citation statements)
references
References 67 publications
(77 reference statements)
17
228
1
3
Order By: Relevance
“…These studies reported delayed overall brain growth, limbic systemspecific volumetric changes, and white matter abnormalities (Li et al, 2012;Lou et al, 1994;Qiu et al, 2013Qiu et al, , 2015Rifkin-Graboi et al, 2013). Such early observations appear to persist into childhood and adolescence, are correlated with affective problems, and may contribute to symptoms in patients with schizophrenia and autism (Buss et al, 2010(Buss et al, , 2012Davis et al, 2013;Du et al, 2013;Sarkar et al, 2014;Zikopoulos and Barbas, 2010).…”
Section: Reprogramming In the Prenatally Stressed Brainmentioning
confidence: 97%
“…These studies reported delayed overall brain growth, limbic systemspecific volumetric changes, and white matter abnormalities (Li et al, 2012;Lou et al, 1994;Qiu et al, 2013Qiu et al, , 2015Rifkin-Graboi et al, 2013). Such early observations appear to persist into childhood and adolescence, are correlated with affective problems, and may contribute to symptoms in patients with schizophrenia and autism (Buss et al, 2010(Buss et al, , 2012Davis et al, 2013;Du et al, 2013;Sarkar et al, 2014;Zikopoulos and Barbas, 2010).…”
Section: Reprogramming In the Prenatally Stressed Brainmentioning
confidence: 97%
“…A small rsfMRI study in six-month old infants (n=24) reported stronger functional connectivity of the amygdala seed region with distributed brain areas of the limbic system and medial prefrontal cortex when their mothers had reported more severe depressive symptoms during the second trimester of pregnancy. Details on maternal psychoactive drug use that may have influenced the observed effects were not reported (Qiu et al, 2015). A recent DWI study described widespread reductions in white matter microstructural maturation of predominantly corticofugal and corticothalamic projection fibers in 20 newborn infants of depressed mothers who had used SSRIs during pregnancy compared to healthy matched control infants.…”
Section: Maternal Mental Illnessmentioning
confidence: 99%
“…Even before birth, the fetal amygdala is affected by his mother's affect (Qiu et al, 2015). Specifically, both depression and cortisol spikes in the mother during pregnancy have been shown to decrease the size of the amygdala later in the infant (Qiu et al, 2015).…”
Section: The Amygdalamentioning
confidence: 99%
“…Specifically, both depression and cortisol spikes in the mother during pregnancy have been shown to decrease the size of the amygdala later in the infant (Qiu et al, 2015). The amygdala matures at six to seven months of age (Vela, 2014).…”
Section: The Amygdalamentioning
confidence: 99%